Phytochemical and Biological Investigations on Curcuma aromatica: A Review - Ahmed, Shamim; Ansari, S.H.; Ali, M.; Bhatt, Deepika; Ansari, Faraz (Pharmacognosy Reviews)
Curcuma aromatica, commonly known as ‘Jangli Haldi’ is a widely cultivated plant in India for its rhizomes. It is commonly used as condiments and as flavouring agents. Medicinally, it has been proven to possess various pharmacological activities like antimicrobial, anti-angiogenic activity, cholerectic activity, anthelminitic activity, antitumour activity, wound healing activity, cytoprotective activity, anti-inflammatory activity and antioxidant effects. Further, studies reveal the presence of various phytochemical constituents mainly essential oils (1,8- cineole, carvone, camphor, borneol, limonene etc.) with curcumin, curcumene and xanthorrhizol. These studies reveal its beneficial therapeutic effects and encourage finding its new uses. It also emphasizes on the fact that these results are made more fruitful by conducting clinical trials.
Keywords: Curcuma aromatica; Phytochemistry; Essential oils; Pharmacological activities